Аналіз характеристик однорідних протоколів маршрутизації бездротових сенсорних мереж - Тимченко, О.; Зеляновский, М. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім. Г.Є. Пухова НАН України, 2010)
Descriptions of popular «homogeneous» protocols of routing of off-wire sensory networks in which all of knots are interpreted identical and evenly take part in the process of routing are examined. Protocols of exchange of information and time of functioning of network are analysed.